USE OF TECHNICAL TRAINING TOOLS FOR ACQUISITION OF FUTURE QUALIFIED WORKERS-PAINTERS WITH THE TECHNOLOGY OF PERFORMANCE OF VARNISH PAINTING - Totska , Olesia; Totskyі Igor (Professional Pedagogics, 2021)
The relevance of the article is due, on the one hand, to the need to organize the educational process in the professional (vocational) education school (hereinafter – P(V)E school) at a level capable of meeting the requirements of the State standard of vocational education for training (advanced training) of workers in the profession of «painter» (a graduate of the P(V)E school with the qualification «painter of the 4th category» must, among other things, know the technology of varnishing), and on the other – the importance of using computer programs and technical training tools (hereinafter – TTT) in the educational process to increase the effectiveness of the formation of students’ skills and abilities to work on the technique of «varnish painting». Aim: to develop an algorithm for preparing and conducting a lesson to acquaint future qualified workers-painters with the technology of varnish painting. Methods: illustrations and demonstrations to visualize the process of varnishing in order to increase attention, increase interest, improve memorization and assimilation of educational material by students. Results: an algorithm for preparing and conducting a lesson on varnish painting has been developed, which has three successive stages: design of a wooden plate in the technique of «Dot painting»; using computer programs Windows Movie Maker, KMPlayer, MS Office PowerPoint, MS Office Word to edit video, defragment it into individual images, prepare a presentation and lesson plan; direct lesson. Conclusions: subject to the previous change of sub-stages and their content, the developed algorithm is effective for painting lessons on other topics and can be used in mastering such disciplines as «Technology of art», «Fundamentals of composition», «Drawing».